UPAYA PENGEMBANGAN PENGETAHUAN AKUNTANSI MELALUI PELATIHAN AYAT JURNAL PENYESUAIAN KEPADA SISWA SMA KRISTOFORUS 1 - Ratna Sari, Vinnetta; Elsa Imelda (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2024)
Community Service Activities at SMA Santo Kristoforus 1 aim to increase high school students’ understanding of adjusting journal entries for trading companies. This activity prioritizes maintaining a pleasant classroom atmophere, ensuring that students do not feel overwhelmed by the high expectations of comprehending the material. This training is needed because there are so many students at Santo Kristoforus 1 High School who have limited knowledge regarding accounting, especially the material on adjusting journal entries for trading companies due to lack of time and lack of resources at Santo Kristoforus 1 High School. Held on 6 6 October and 11 October 2023 offline (face to face), the activity involved students in grades 10, 11 and 12. The material was presented through theoretical explanations, practice questions and the game